Reorganization of Functional Connectivity of the Language Network in Patients with Brain Gliomas - Briganti, C.; Sestieri, C.; Mattei, P.A.; Esposito, R.; Galzio, R.J.; Tartaro, A.; Romani, G.L.; Caulo, M. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: fcMRI measures spontaneous and synchronous fluctuations of BOLD signal between spatially remote brain regions. The present study investigated potential LN fcMRI modifications induced by left hemisphere brain gliomas. MATERIALS AND METHODS: We retrospectively evaluated fcMRI in 39 right-handed patients with a left hemisphere brain glioma and 13 healthy controls. Patients and controls performed a verb-generation task to identify individual BOLD activity in the left IFG (Broca area); the active region was used as seed to create whole-brain background connectivity maps and to identify the LN (including bilateral regions of the IFG, STS, and TPJ) following regression of task-evoked activity. We assessed differences between patients and controls in the pattern of functional connectivity of the LN, as well as potential effects of tumor position, histopathology, and volume. RESULTS: Global fcMRI of the LN was significantly reduced in patients with tumor compared with controls. Specifically, fcMRI was significantly reduced within seed regions of the affected hemisphere (left intrahemispheric fcMRI) and between the TPJ of the 2 hemispheres. In patients, the left TPJ node showed the greatest decrease of functional connectivity within the LN. CONCLUSIONS: The presence of a brain tumor in the left hemisphere significantly reduced the degree of fcMRI between language-related brain regions. The pattern of fcMRI was influenced by tumor position but was not restricted to the area immediately surrounding the tumor because the connectivity between remote and contralateral areas was also affected. BOLDblood oxygen level–dependentCScentrum semiovaleFCfunctional connectivityfcMRIfunctional connectivity MRIIFGinferior frontal gyrusLNlanguage networkSTSsuperior temporal sulcusTPJtemporoparietal junctionV1visual areaWHOWorld Health Organization